Pemahaman Critical Thinking, Design Thinking dan Problem Solving dalam Proses Desain - Sofiana, Yunida (Humaniora, 2014)
The task of the designer is not limited to beautify the aesthetic appearance of a form, but more complex and down to the root of the problem. Based on observations made at the educational institution, all this time, the process of designing is carried out in the world of education, discusses the more common problems and it simply just to beautify a form. The purpose of this study is to revitalize the importance of the design process that is accompanied by a pattern of critical and creative thinking in finding solutions to design problems. So that the resulting design, and variations will have a better quality after going through deeper thinking. The research method is descriptive-qualitative research that are taken from various sources of books, internet and student assignments. The data are summarized and analyzed and made a conclusion.